Ensuring Security in Multi-Tag Backscatter Communication Systems - You, Zilin; Liang, Zhihong; Suo, Siliang; Mai, Lifeng; Lin, Qiaoling (EAI Endorsed Transactions on Scalable Information Systems, 2026)
This paper studies the security performance of a multi-tag backscatter communication system, where a reader exchanges its information with multiple distributed tags in the presence of an eavesdropper. The system security performance is assessed using the secrecy outage probability (SOP), which quantifies the likelihood that the system secrecy capacity drops below a specified threshold. The paper provides a mathematical analysis on the communication links, considering Rayleigh fading, and investigates the effect of system monostatic and bistatic RFID configurations on the overall security. An optimal tag selection scheme is proposed to maximize the secrecy capacity by choosing the tag with the best link between the reader and the eavesdropper. Moreover, an analytical expression is derived for the system SOP, which incorporates the joint probability distributions of channel gains and the asymptotic SOP is provided as the signal-to-noise ratio increases. Simulation results are presented to verify the theoretical analysis, where the simulation results closely match the analytical predictions, confirming the accuracy of the proposed SOP analysis. Moreover, the asymptotic analysis offers an upper bound on the outage probability, consistent with theoretical analysis.
Keywords: Power data network; multi-tag; secure transmission; backscatter communication